HUBUNGAN ANTARA EFIKASI DIRI DENGAN BURNOUT PADA GURU SEKOLAH LUAR BIASA (SLB) DI YOGYAKARTA - Widyana, Rahma; Nurwahyuni, Adistya (Jurnal Psikohumanika, 2024)
This research aims to determine the relationship between self-efficacy and burnout in special school (Sekolah Luar Biasa or SLB) teachers in Yogyakarta, and to examine differences in the level of burnout of SLB teachers in terms of gender, age, and duration of teaching. The research subjects were 108 SLB teachers in Yogyakarta with an age range of 25-50 years. The research data was collected with the General Self Efficacy (GSE) Scale and the Burnout Scale. Based on data analysis results, a correlation coefficient (rxy) = -0.418 (p < 0.050) was generated, indicating that the proposed hypothesis was accepted; there was a negative correlation between self-efficacy and burnout in special school teachers (SLB) in Yogyakarta. The coefficient of determination (R2) is 0.175, so the contribution of self-efficacy is 17.5% to burnout. The study results also showed differences in burnout levels in terms of age and duration of teaching. Subjects aged 38-50 years had lower burnout than subjects aged 25-37 years. Subjects who have taught or worked for more than 15 years have lower burnout than teachers who have taught or worked for less than 15 years. There was no difference in burnout levels in terms of gender.